Identification of regulatory elements mediating responses of SOD and cystatin transcripts to salt stress and nitric oxide in soybean nodules - Jacobs, Frans Alexander (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.